Evaluation of the phytochemical and hemostatic potential of Jatropha multifida - DOUGNON, T. VICTORIEN; KLOTOE, J.R.; SEGBO, JULIEN A. GAÉTAN (My University, 2012)
Jatropha multifida is a plant traditionally recognized for its medicinal properties. This study was undertaken not only to assess the hemostatic potential of the sap of J. multifida, but also to elucidate its chemical profile. Wistar rats were injured at various locations and time of bleeding was evaluated based on the addition of J. multifida’s sap or distilled water. Phytochemical study was performed on sap. J. multifida’s sap significantly reduced bleeding time. Indeed, more blood flow was noticed on the side that received physiological water than the one which received the sap. This is even truer when the cut is deep with times of bleeding reduction of 39.06, 47.89, and 46.68%, respectively for superficial wounds, saphenous vein, and the femoral vein clippings. The phytochemical screening of J. multifida showed the presence of tannins, flavonoids, saponins, leucoanthocyanes, mucilage and reducing compounds. The power of the hemostatic sap is explained by the strong presence of tannins and flavonoids. All this proves that using the sap of J. multifida in traditional medicine is justified.
Keywords: Hemostatic; Wistar rats; tannins; flavonoids; bleeding; Jatropha multifida.